HLA-Associated Alterations in Replication Capacity of Chimeric NL4-3 Viruses Carrying gag-protease from Elite Controllers of Human Immunodeficiency Virus Type 1 - Miura, Toshiyuki; Brockman, Mark A.; Brumme, Zabrina L.; Brumme, Chanson J.; Pereyra, Florencia; Trocha, Alicja; Block, Brian L.; Schneidewind, Arne; Allen, Todd M.; Heckerman, David; Walker, Bruce D. (Journal of Virology, 2009)
Human immunodeficiency virus type 1 (HIV-1)-infected persons who maintain plasma viral loads of <50 copies RNA/ml without treatment have been termed elite controllers (EC). Factors contributing to durable control of HIV in EC are unknown, but an HLA-dependent mechanism is suggested by overrepresentation of “protective” class I alleles, such as B*27, B*51, and B*57. Here we investigated the relative replication capacity of viruses (VRC) obtained from EC (n = 54) compared to those from chronic progressors (CP; n = 41) by constructing chimeric viruses using patient-derived gag-protease sequences amplified from plasma HIV RNA and inserted into an NL4-3 backbone. The chimeric viruses generated from EC displayed lower VRC than did viruses from CP (P < 0.0001). HLA-B*57 was associated with lower VRC (P = 0.0002) than were other alleles in both EC and CP groups. Chimeric viruses from B*57+ EC (n = 18) demonstrated lower VRC than did viruses from B*57+ CP (n = 8, P = 0.0245). Differences in VRC between EC and CP were also observed for viruses obtained from individuals expressing no described “protective” alleles (P = 0.0065). Intriguingly, two common HLA alleles, A*02 and B*07, were associated with higher VRC (P = 0.0140 and 0.0097, respectively), and there was no difference in VRC between EC and CP sharing these common HLA alleles. These findings indicate that cytotoxic T-lymphocyte (CTL) selection pressure on gag-protease alters VRC, and HIV-specific CTLs inducing escape mutations with fitness costs in this region may be important for strict viremia control in EC of HIV.